2018
DOI: 10.3389/fenvs.2018.00024
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Potential of Microorganisms for Managing Arsenic Contamination: A Feasible and Sustainable Approach

Abstract: Arsenic (As) contamination is a serious issue throughout the world. The scale of problem is being realized to be even greater with the discovery of new As contaminated regions with time. Rice is a staple crop across the world with approximately half of the world population dependent on rice for their daily dietary intake especially in Southeast Asian countries. It is not only the consumption of rice grains but also food products based on rice, which contribute toward As exposure to humans. Plant growth promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(25 citation statements)
references
References 98 publications
0
25
0
Order By: Relevance
“…(one isolate). Arsenic-tolerant microorganisms can promote plant growth and uptake of arsenic in arsenic-contaminated environments and are thus important in phytoremediation approaches ( Mesa et al, 2017 ; Upadhyay et al, 2018 ). Some of the isolated strains from the present study might thus be used as inoculants to improve phytoremediation of arsenic-contaminated systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(one isolate). Arsenic-tolerant microorganisms can promote plant growth and uptake of arsenic in arsenic-contaminated environments and are thus important in phytoremediation approaches ( Mesa et al, 2017 ; Upadhyay et al, 2018 ). Some of the isolated strains from the present study might thus be used as inoculants to improve phytoremediation of arsenic-contaminated systems.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, arsenic-tolerant microbes are important drivers of many other contaminant removal processes like nitrogen or sulfate removal in treatment peatlands and other high-arsenic environments. They can, moreover, promote plant growth and phytoremediation in high-arsenic environments ( Mesa et al, 2017 ; Upadhyay et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between plants and microorganisms in the rhizosphere play a key role in growth of plants, and in nutrient uptake and transport [48]. Several studies have shown that plants’ adaptation to local environmental stress is closely related to the microorganisms that are in their surroundings [49].…”
Section: Discussionmentioning
confidence: 99%
“…Several documented evidences have reported the isolation of several genera such as Exiguobacterium, Aeromonas, Planococcus, Bacillus, Pseudomonas, Escherichia, Acinetobacter that illustrated high tolerance capacity for arsenic (0-100mM arsenate) (Upadhyay et al 2018;Taran et al 2019).…”
Section: Introductionmentioning
confidence: 99%